2022
DOI: 10.1002/jcsm.12964
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbes and muscle function: can probiotics make our muscles stronger?

Abstract: Evidence suggests that gut microbiota composition and diversity can be a determinant of skeletal muscle metabolism and functionality. This is true in catabolic (sarcopenia and cachexia) or anabolic (exercise or in athletes) situations. As gut microbiota is known to be causal in the development and worsening of metabolic dysregulation phenotypes such as obesity or insulin resistance, it can regulate, at least partially, skeletal muscle mass and function. Skeletal muscles are physiologically far from the gut. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 120 publications
4
80
0
Order By: Relevance
“…In contrast, we saw no tangible benefits arising from strain 62. Over recent years, several studies have tested the health effects of probiotic bacteria in elderly animals [see Giron et al ( 29 ) for a recent review]. To our knowledge, none of this research has applied conditions of food restriction, even though lower food intake contributes to sarcopenia and frailty in elderly people ( 1 , 65 69 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we saw no tangible benefits arising from strain 62. Over recent years, several studies have tested the health effects of probiotic bacteria in elderly animals [see Giron et al ( 29 ) for a recent review]. To our knowledge, none of this research has applied conditions of food restriction, even though lower food intake contributes to sarcopenia and frailty in elderly people ( 1 , 65 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the gut microbiota and skeletal muscle engage in cross-talk ( 5 , 16 20 ), which leads us to hypothesize that strategies targeting gut community composition and function could help frail elderly individuals improve their skeletal muscle health. Indeed, some probiotics have been demonstrated to modulate inflammation, metabolic issues (e.g., age-related declines in insulin sensitivity), and muscle function in juvenile rodents ( 21 24 ), adult rodents ( 25 ), and humans of various ages ( 26 28 ) [for a review, see Giron et al ( 29 )]. The benefits of probiotics have also been investigated using rodent models of aging [SAMP-8 ( 30 32 ) and D-galactose ( 33 )] and animal models of cachexia ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no complete studies investigating the mechanism by which probiotic supplementation improves CK and myoglobin. However, in a retrospective study, probiotics were found to help increase short-chain fatty acids (SCFA) in the gut, which in turn increased glycogen concentration and protein digestibility, and promoted muscle repair and recovery [ 60 ]. A past animal study also showed that L. plantarum Tana supplementation for four weeks significantly improved exercise performance and reduced post-exercise blood lactate and blood ammonia levels, as well as CK activity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protein expression of GLUT4 was found to be increased in skeletal muscle, which may be involved in the mechanism of EA on insulin sensitivity. In addition, the gut microbiota is known to be causal in the development of obesity/insulin resistance ( 111 ). A recent study showed that EA intervention decreased body weight, probably through regulating gut microbiota in PCOS rats ( 112 ).…”
Section: Potential Mechanisms Of Acupuncture Affecting Pcos-related S...mentioning
confidence: 99%